Soziale Rückvergütung - das Projekt „Lateinamerika“ der Spanisch-Deutschen HNO-Gesellschaft (SDGHNO) = Social reimbursement-the Spanish-German ENT Society's (SDGHNO) Latin America project - Offergeld, Christian; Zahnert, Thomas; Caro, J.; Prieto, J. A.; Centeno, J.; Laszig, Roland; Schwager, K.; Bockmühl, Ulrike; Praetorius, Mark; Baumann, Ingo; Bootz, Friedrich; Schmidt, T.; et al. (HNO, 2019)
Nowadays, social projects are usually oriented in such a way that after a given period of time, they can either support themselves independently or even allow a pecuniary reimbursement. In the latter case, experts speak of a profit-oriented reimbursement. On the other hand, there is so-called social reimbursement, which in contrast to the abovementioned form is not profit oriented, but, for example, considers its task fulfilled by the fact of successful knowledge transfer. The Spanish-German Society for ENT Medicine and Head and Neck Surgery (SDGHNO) launched the Latin America project in 2001 under the patronage of the then President Prof. Dr. Wolfgang Draf (Fulda). The goal of the SDGHNO was and is to create a professional as well as cultural platform for Spanish- and German-speaking ENT doctors. This platform can and should be used for professional purposes, e.g., for knowledge transfer. Since the beginning of its existence, the Latin America project has thus brought numerous scientific events into being and created specific contacts which have lasted until today or have even been continued and further developed. Particularly successful examples are Chile, Colombia, and Peru. This is a vivid example of social reimbursement, because the participating German-speaking members/speakers carried out their tasks on an entirely voluntary basis. Thus, the SDGHNO did not bear any travel, catering, or accommodation costs. The activities of the SDGHNO within the framework of the Latin America project are explained.